Impaired thiol/disulfide homeostasis in patients with mild acute pancreatitis - Uyanıkoğlu, Ahmet; Sabuncu, Tevfik; Yıldız, Rukiye; Cindioğlu, Çiğdem; Kirmit, Adnan; Erel, Özcan (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The aim of this study was to compare the dynamic thiol/disulfide (SS) homeostasis and ischemia-modified albumin (IMA) concentration between healthy subjects and patients with mild acute pancreatitis (AP). Materials and Methods: A total of 28 patients with AP (AP group) and 35 age- and sex-matched healthy individuals (control group) were included in this study. Serum thiols/SS and IMA concentrations were measured and compared between the two groups. Results: The mean serum native thiol (SH) and total thiol (TT) levels were significantly lower in the AP group than in the control group (224.7±80.3 μmol/L vs. 314.66±87.5 μmol/L, p<0.001 and 273.3±76.8 vs. 346.9±79 μmol/L, p<0.001, respectively). SS levels were significantly higher in the AP group than in the control group (24.2±11.1 μmol/L vs. 16.1±9.9 μmol/L, p<0.054). There were no differences in the IMA concentration and the mean IMA/albumin ratio (IMAR) between both the groups. Conclusion: We found that mild AP may affect serum thiol and SS levels, and cause impaired thiol/SS homeostasis.